Improved mechanical and microwave absorption properties of SiCf/SiC composites with SiO2 filler. Issue 10 (15th May 2021) - Ren, Zhaowen; Zhou, Wancheng; Qing, Yuchang; Duan, Shichang; Pan, Haijun; Zhou, Yingying
Abstract: SLF and KD-S SiC fibers were used to fabricate SiCf /SiC composites by precursor impregnation and pyrolysis (PIP) method. To simultaneously improve both the mechanical and electromagnetic wave absorption properties of SiCf /SiC composites, the SiO2 fillers were mixed into the PSC/xylene precursor solution as inert filler. In this research, the effects of SiO2 filler on the micro morphologies, XRD patterns, mechanical and dielectric property were investigated. The results exhibit that the flexural strength of the SLF and KD-S SiCf /SiC composites was improved from 167.69 MPa to 241.95 MPa and 248.16 MPa–324.87 MPa with SiO2 filler, respectively. The lower complex permittivity and better impedance matching are attributed to a broken conductive network in the SiC matrix, which is caused by SiO2 filler. Therefore, the reflection loss values of SLF SiCf /SiC composites with SiO2 filler were approach at −40 dB, and the KD-S SiCf /SiC composites with SiO2 filler of that over −12 dB. The effective absorption bandwidths of SLF and KD-S SiCf /SiC composites with SiO2 filler are 3.44 GHz and 2.75 GHz, respectively.